T(FH) cells accumulate in mucosal tissues of humanized-DRAG mice and are highly permissive to HIV-1 - Allam, Atef (Sci Rep, 2015)
CD4(+) T follicular helper cells (T(FH)) in germinal centers are required for maturation of B-cells. While the role of T(FH)-cells has been studied in blood and lymph nodes of HIV-1 infected individuals, its role in the mucosal tissues has not been investigated. We show that the gut and female reproductive tract (FRT) of humanized DRAG mice have a high level of human lymphocytes and a high frequency of T(FH) (CXCR5(+)PD-1(++)) and precursor-T(FH) (CXCR5(+)PD-1(+)) cells. The majority of T(FH)-cells expressed CCR5 and CXCR3 and are the most permissive to HIV-1 infection. A single low-dose intravaginal HIV-1 challenge of humanized DRAG mice results in 100% infectivity with accumulation of T(FH)-cells mainly in the Peyer’s patches and FRT. The novel finding of T(FH)-cells in the FRT may contribute to the high susceptibility of DRAG mice to HIV-1 infection. This mouse model thus provides new opportunities to study T(FH)-cells and to evaluate HIV-1 vaccines.